Ulama Nusantara’s Legacy: Study of Hadith in the Book of Nuṣūṣ al-Akhyār fī al-Ṣawm wa al-Ifṭār in Hasan Hanafi's Hermeneutic Perspective - Anam, Wahidul; Sulaeman, Mubaidi; Ali, Zezen Zainul (Ulumuna, 2024)
This research examines the Prophetic traditions contained in the book "Nuṣūṣ al-Akhyār fī al-Ṣawm wa al-Ifṭār" authored by K.H. Maimun Zubair, which is used as the basis of argumentation in determining the beginning of Ramadan and Eid al-Fitr. This research uses Hasan Hanafi's hermeneutical method, which includes a critical analysis of the sanad, the matan of the hadith, the context of the emergence of the hadith, and its relevance. The results of the study found that there were variations in the quality of the hadith sanad in the book "Nuṣūṣ al-Akhyār fī al-Ṣawm wa al-Ifṭār," including the categories of shahih and hasan lighairi (good but not perfect in sanad). However, the overall text of the traditions in the book is considered good quality. This indicates the potential of the traditions contained in the book "Nuṣūṣ al-Akhyār fī al-Ṣawm wa al-Ifṭār" to be used as evidence in determining the laws of Islamic law. In addition, it is essential to understand the hadith text in depth, including its original meaning, historical context, and relevance to the context of life today.